2018
DOI: 10.1093/nar/gky140
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and mutagenic properties of alkyl phosphotriester lesions in Escherichia coli cells

Abstract: Exposure to many endogenous and exogenous agents can give rise to DNA alkylation, which constitutes a major type of DNA damage. Among the DNA alkylation products, alkyl phosphotriesters have relatively high frequencies of occurrence and are resistant to repair in mammalian tissues. However, little is known about how these lesions affect the efficiency and fidelity of DNA replication in cells or how the replicative bypass of these lesions is modulated by translesion synthesis DNA polymerases. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 33 publications
6
32
1
Order By: Relevance
“…In addition to methyl base adducts, some methylating agents also react with the DNA phosphate backbone to form methyl DNA phosphate adducts—B 1 pMeB 2 (Figure 2, see details in Section 3.1). B 1 pMeB 2 adducts were demonstrated to induce TT→GT and TT→GC mutations [71], inhibit RNA synthesis [72], and affect the binding affinity of DNA to other macromolecules [73].…”
Section: Smoking-related Dna Adducts In Humansmentioning
confidence: 99%
“…In addition to methyl base adducts, some methylating agents also react with the DNA phosphate backbone to form methyl DNA phosphate adducts—B 1 pMeB 2 (Figure 2, see details in Section 3.1). B 1 pMeB 2 adducts were demonstrated to induce TT→GT and TT→GC mutations [71], inhibit RNA synthesis [72], and affect the binding affinity of DNA to other macromolecules [73].…”
Section: Smoking-related Dna Adducts In Humansmentioning
confidence: 99%
“…5-Hydroxymethyluracil (5hmU) blocks replication by 20%, but it is not mutagenic in human cells [60]. The S p alkyl phosphotriester ( S p -alkyl-PTE) lesions display comparable replication bypass efficiency to unmodified DNA in E. coli ; S p -Me-PTE is mutagenic causing TT>GT (50%) and TT>GC (15%) mutations [61]. In contrast, R p -alkyl-PTEs block DNA replication (30–70%) but are not mutagenic [61].…”
Section: Discussion On Individual Modificationsmentioning
confidence: 99%
“…The S p alkyl phosphotriester ( S p -alkyl-PTE) lesions display comparable replication bypass efficiency to unmodified DNA in E. coli ; S p -Me-PTE is mutagenic causing TT>GT (50%) and TT>GC (15%) mutations [61]. In contrast, R p -alkyl-PTEs block DNA replication (30–70%) but are not mutagenic [61]. Interestingly, n Pr- and n Bu-PTEs exhibit higher bypass efficiencies than Me- and Et-PTEs [61].…”
Section: Discussion On Individual Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1921 One recent study suggested that the bacterial O 6 -alkylguanine transferase Ada was required for the TT to GT or GC mutations induced by the methyl DNA phosphate adduct lesion. 22 Previous studies from our laboratory have shown that NNK-derived electrophilic diazonium ions 10 – 12 (Scheme 1) react with the nonbridging oxygens of the DNA internucleotide phosphate moiety. 2325 Both POB and PHB phosphate adducts were quantified in rat tissues at relatively high levels.…”
Section: Introductionmentioning
confidence: 99%